The Effect Of Person Organization Fit On Employee Performance With Organizational Commitment Mediation Variables - SUCIATI, Audina Sarah; ERLINA, R.R.; AHADIAT, Ayi (International Journal of Environmental, Sustainability, and Social Science, 2021)
The role of employees in fulfilling the company's strategy is shown through performance. How well the performance shown by employees is adjusted to the standards set by the company and can be determined by the management of the performance itself. It is essential for companies to carry out a performance management process and then conduct an employee performance appraisal within a certain period of time. So that in the end, the performance of an organization depends on the performance of its employees. This study aimed to determine the effect of personal organization fit on employee performance and the indirect effect through organizational commitment. This study uses quantitative methods by distributing questionnaires in data collection. The sample of this study was taken from the results of questionnaires to employees of as many as 105 people. The analytical tool used is path analysis (path analysis). The results of this study support the four hypotheses proposed: first, person organization fit has a positive and significant effect on employee performance. Second, personal organization fit positively and significantly affects organizational commitment. Third, organizational commitment has a positive and significant effect on employee performance, and fourth organizational commitment mediates the effect of the personal organization fit on employee performance. So, paying attention to personal organization fit and organizational commitment to improving employee performance is necessary